2015
DOI: 10.1002/adfm.201502429
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Circularly Polarized Photocatalytic Activity in Nanogapped Gold–Silver Chiroplasmonic Nanostructures

Abstract: Gold‐gap‐silver nanostructures (GGS NSs) with interior nanobridged gaps are enantioselectively fabricated. Guided by l/d‐cysteine, the GGS‐L/D (L/D represents l/d‐cysteine) NSs show reversed plasmon‐induced circular dichroism (CD) signals in the visible region. It is found that the nanogap plays a key role in the plasmonic CD of GGS NSs and the chiroptical response can be tailored by adjusting the amount of cysteine. The anisotropy factor of GGS‐L/D NSs with a 0.5 nm interior gap at 430 nm is as high as ≈0.01.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
112
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 61 publications
3
112
0
Order By: Relevance
“…From the high resolution TEM image, it is confirmed that there is no distinct gap between the Au core and the Ag shell layer (Figure b,ii), which is consistent with our previous observation on Au@BDT@Ag core–shell rod‐like nanoprobes . The Au@BDT@Ag suspension shows a yellow color and the corresponding LSPR peak blueshifts to 426 nm (Figure c,iii), which further indicates the successful coating of the Ag shell . The calculated extinction spectrum of a Au@Ag core–shell NP (24 nm for the diameter of the Au core and 20 nm for the Ag shell thickness, without internal gaps in the simulation model) by the finite difference time domain (FDTD) method well fits the experimental extinction spectrum (dashed line in Figure c), which also suggests that no internal gaps exist in the Au@BDT@Ag NPs.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…From the high resolution TEM image, it is confirmed that there is no distinct gap between the Au core and the Ag shell layer (Figure b,ii), which is consistent with our previous observation on Au@BDT@Ag core–shell rod‐like nanoprobes . The Au@BDT@Ag suspension shows a yellow color and the corresponding LSPR peak blueshifts to 426 nm (Figure c,iii), which further indicates the successful coating of the Ag shell . The calculated extinction spectrum of a Au@Ag core–shell NP (24 nm for the diameter of the Au core and 20 nm for the Ag shell thickness, without internal gaps in the simulation model) by the finite difference time domain (FDTD) method well fits the experimental extinction spectrum (dashed line in Figure c), which also suggests that no internal gaps exist in the Au@BDT@Ag NPs.…”
Section: Resultssupporting
confidence: 88%
“…[63] The Au@BDT@Ag suspension shows a yellow color and the corresponding LSPR peak blueshifts to 426 nm (Figure 2c,iii), which further indicates the successful coating of the Ag shell. [27,64,65] The calculated extinction spectrum of a Au@Ag core-shell NP (24 nm for the diameter of the Au core and 20 nm for the Ag shell thickness, without internal gaps in the simulation model) by the finite difference time domain (FDTD) method well fits the experimental extinction spectrum (dashed line in Figure 2c), which also suggests that no internal gaps exist in the Au@BDT@Ag NPs. The calculated electric field intensity (E/E 0 ) map shows strong near-field enhancements mainly distributed on the external surface of the Ag shell (inset in Figure 2c), which implies a potential strong Raman enhancement for any molecule adsorbed on the Ag shell surface.…”
Section: Figure 2amentioning
confidence: 65%
“…With the fast development of bottom‐up and top‐down approaches for the sample synthesis and fabrication, the chiral study has been generally extended from traditional molecules to metal nanostructures, such as noble metal nanoparticle (NPs), chiral metamaterials and chiral photonic crystal . Several promising applications, such as biosensing, chiral catalysis, polarization tuning, and ultrasensitive detections, have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Accurate fabrication of regiospecific plasmonic assemblies is crucial for understanding the coherent interactions among constituent nanoparticles. [1][2][3][4][5] Accurate fabrication of regiospecific plasmonic assemblies is crucial for understanding the coherent interactions among constituent nanoparticles.…”
mentioning
confidence: 99%
“…
Plasmonic nanoparticles and their assemblies have become prominent building blocks for widespread applications in nanotechnology such as metamaterials, biosensors, and photonic and optoelectronic devices. [1][2][3][4][5] Accurate fabrication of regiospecific plasmonic assemblies is crucial for understanding the coherent interactions among constituent nanoparticles. [6][7][8][9] Therefore, various surface modification strategies of plasmonic nanoparticles have been proposed toward their self-assembly in a prescribed and directional manner.
…”
mentioning
confidence: 99%